(untitled) (Revista ARTA, 2025)
The article analyzes the creativity of Veronica Coteleva Toma against the background of the artistic transformations that took place in the Republic of Moldova after the 1990s, a period during which the art scene opened up to stylistic diversity and expressive freedom. Her artistic formation is grounded in a solid tradition of plastic arts, cultivated within the spirit of the national school of painting and enriched through a nuanced assimilation of European artistic values. In her oeuvre, the artist harmoniously merges the heritage of classical painting with a contemporary sensibility, giving rise to a visual poetics characterized by sincerity and refinement. Still lifes, rural landscapes, and feminine portraits serve as pretexts for a silent meditation on the beauty and transience of existence. Through a mature and introspective visual language, Veronica Coteleva Toma articulates an art of inner equilibrium, where the vibrancy of color and the controlled pictorial gesture unveil calm, distilled emotions. Her creation contributes significantly to the enrichment of the national cultural patrimony, asserting itself through authenticity, delicacy, and a restrained yet deeply resonant expressiveness.